Evaluation of oral drug adherence in patients with oncological pain in Pernambuco reference hospital - Dayseanne B. SILVA; Juvanier R. CRUZ; Narcisa C. SILVA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objectives: The aim of this study was to describe the profile of patients with cancer pain using oral opioids, to evaluate the therapeutic adherence of these patients and to identify the factors associated with it. Methods: It was a cross-sectional study carried out at the Pharmacy of the Hospital de Câncer de Pernambuco, from March to September 2019. Each patient were selected for convenience and were interviewed once, and the Medicines Evaluation Questionnaire (BMQ) was used to determine adherence and FACS for determine the socioeconomic, demographic and clinical profile. The data was analyzed using the Statistical Package for Social Sciences (SPSS) program. Results: In total, 46 patients were interviewed, aged between 19 and 82 years, 59% did not have complete elementary school, 74% had family income equal or less than 1 minimum wage and 71% classified as non-adherent, with the domain "recall screen" the most scored (84%). Patients using controlled-release medications (p = 0.0000352) and with higher levels of education (p = 0.016) obtain better adherence results in the BMQ questionnaire. Conclusions: Through the study it was possible to identify a high incidence of patients not adhering to drug therapy and their socioeconomic profile, highlighting the need for political and institutional interventions. Due to the scarcity of publications, further studies are needed to determine adherence factors in patients with cancer pain.